2022
DOI: 10.7554/elife.74591
|View full text |Cite
|
Sign up to set email alerts
|

Neural excursions from manifold structure explain patterns of learning during human sensorimotor adaptation

Abstract: Humans vary greatly in their motor learning abilities, yet little is known about the neural mechanisms that underlie this variability. Recent neuroimaging and electrophysiological studies demonstrate that large-scale neural dynamics inhabit a low-dimensional subspace or manifold, and that learning is constrained by this intrinsic manifold architecture. Here, we asked, using functional MRI, whether subject-level differences in neural excursion from manifold structure can explain differences in learning across p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 79 publications
(110 reference statements)
5
32
0
Order By: Relevance
“…Specifically, we found that the cerebellum was overwhelmingly EL-aligned, consistent with its established role in implicit learning through sensory prediction errors (Wolpert et al, 2011; Taylor and Ivry, 2014). Our observation that large segments of the dorsal-attention network were EL aligned is likewise consistent with our previous findings that the engagement of the dorsal-attention network is associated with better performance during visuomotor adaptation learning (Areshenkoff et al, 2022). By contrast, we found that the putamen and accumbens were RL-aligned, consistent with their role in reward-based learning (Knowlton et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we found that the cerebellum was overwhelmingly EL-aligned, consistent with its established role in implicit learning through sensory prediction errors (Wolpert et al, 2011; Taylor and Ivry, 2014). Our observation that large segments of the dorsal-attention network were EL aligned is likewise consistent with our previous findings that the engagement of the dorsal-attention network is associated with better performance during visuomotor adaptation learning (Areshenkoff et al, 2022). By contrast, we found that the putamen and accumbens were RL-aligned, consistent with their role in reward-based learning (Knowlton et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…To reduce the influence of large individual differences in functional connectivity that can obscure any task-related changes (Fig. 1D; see also [55]), all connectivity matrices were centered according to a Riemmanian manifold approach (see Materials and Methods; [56][57][58]). To demonstrate the effect of this centering procedureand its importance for elucidating learning-related effects in the data-we projected participants' individual covariance matrices, both before and after centring, using uniform manifold approximation (UMAP; [59]).…”
Section: Resultsmentioning
confidence: 99%
“…We centered the connectivity matrices according to a previously described procedure that leverages the natural geometry of the space of the covariance matrices [56][57][58]. First, a grand mean covariance matrix, Sgm , was computed by taking the geometric mean covariance matrix across all participants and epochs.…”
Section: Methodsmentioning
confidence: 99%
“…6A highlights the learning curves for two example subjects: An individual who learned the hidden shape quite rapidly (a ‘fast learner’ in green) and a second individual who only gradually learned to trace the hidden shape (a ‘slow learner’ in red). To quantify this variation in subject performance, we opted for a pure data-driven approach and performed functional principal component analysis (fPCA; 75 ) on subjects’ learning curves, which allowed us to isolate the dominant patterns of subject variability see Methods for further details; see also 63 . Using this fPCA approach, we found that a single component — encoding overall learning — captured the majority (∼75%) of the variability in subjects’ learning curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the benefits (and general necessity) of this centering approach, see Fig. 2, and for an additional overview, see 63 .…”
Section: Methodsmentioning
confidence: 99%